Groundwater Potential Assessment Using Integrated Geospatial and Analytic Hierarchy Process Techniques (AHP) in Chemoga Watershed, Upper Blue Nile Basin, Ethiopia - Samuel Berihun Kassa; Fasikaw Atanaw Zimale; Arega Mulu; Tadege Aragaw Worku; Mindesilew Lakew Wossene; Taye Minichil Meshesha; Yoseph Buta Hailu; Tadele F. Aman; Mekash S. Kifelew; Habtamu Asrat Mekonnen (Air, Soil and Water Research)
Groundwater is an invaluable natural resource that sustains human life and supports the economic development of nations. However, its unsustainable utilization has emerged as a critical issue, particularly in developing countries. This study investigates the groundwater potential of the Chemoga watershed to address these challenges. Conventional groundwater assessments have typically relied on labor-intensive and time-consuming field surveys, which are resource-demanding and often fail to provide accurate estimates due to the inherent complexity of groundwater systems. In response, this research utilizes geospatial and analytic hierarchy process (AHP) techniques to assess groundwater potential in the Chemoga Watershed, aiming to overcome these challenges. Eight critical biophysical and environmental factors: geology, slope, rainfall, land use/land cover (LULC), soil type, elevation, lineament density, and drainage density were selected for analysis using Saaty’s AHP methodology. Data was gathered from satellite imagery, existing thematic maps, local water offices, and national meteorological agencies. The integration of these thematic maps was performed through a weighted overlay analysis using ArcGIS 10.8, which resulted in the delineation of groundwater potential zones (GWPZ). The model was validated by cross-referencing the generated GWPZ with existing data from dug wells and boreholes. The results reveal five groundwater potential zones: very high (0.73%), high (24.39%), moderate (43.38%), poor (31.25%), and very poor (0.25%). The most suitable zones are in the south, southeast, and southwest of the watershed, particularly near Debre Markos Town. These high-potential zones were validated with a significant 81.5% match to ground truth data from shallow wells. The findings of this study provide crucial insights for decision-makers, enabling the formulation of more effective groundwater management strategies. By identifying cost-effective and suitable well sites, this research contributes to ensuring a sustainable water supply for Debre Markos Town.